FIRM SIZE DAN FAKTOR LAIN YANG MEMENGARUHI CASH HOLDING - Joane Gabriela Purwakusuma; Viriany Viriany (Fakultas Ekonomi, Universitas Tarumanagara, 2026)
This research aims at how the effect of Firm Size, Liquidity, Profitability, and Leverage toward cash holding on plantations and food crops industry listed on the Indonesia Stock Exchange (IDX) in the 4 years period, from 2018 to 2021. The sample was chosen through the purposive sampling technique, and it consisted of 9 valid company’s data. Data processing techniques using multiple regression analysis that helped by EViews 12 edition program and Microsoft Excel 2019. Regression model used in this research is random effect model. The results of this study indicate that liquidity has a positive and significant effect on cash holding. Meanwhile, firm size, profitability, and leverage has no significant effect on cash holding. The implication of this research is the need to increase the supervision of cash holding and cash control of the company, that will increase the optimalization of company’s cash holding. Which will bring a good branding for the investors and stakeholders.